2004
DOI: 10.1163/156856204323046843
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage behavior on surface-modified polyurethanes

Abstract: Adherent macrophages and foreign body giant cells (FBGCs) are known to release degradative molecules that can be detrimental to the long-term biostability of polyurethanes. The modification of polyurethanes using surface modifying endgroups (SMEs) and/or the incorporation of silicone into the polyurethane soft segments may alter macrophage adhesion, fusion and apoptosis resulting in improved long-term biostability. An in vitro study of macrophage adhesion, fusion and apoptosis was performed on polyurethanes mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 30 publications
2
56
1
Order By: Relevance
“…23,24 In our previous study, we investigated the effect of PDMS in the soft segment and SME of the polyurethanes on macrophage adhesion and activity. 25 We reported that silicone modification did not affect monocyte/macrophage adhesion on modified and unmodified polyurethanes. However, silicone modification promoted macrophage fusion and apoptosis on modified materials.…”
Section: Introductionmentioning
confidence: 86%
“…23,24 In our previous study, we investigated the effect of PDMS in the soft segment and SME of the polyurethanes on macrophage adhesion and activity. 25 We reported that silicone modification did not affect monocyte/macrophage adhesion on modified and unmodified polyurethanes. However, silicone modification promoted macrophage fusion and apoptosis on modified materials.…”
Section: Introductionmentioning
confidence: 86%
“…[30] Biomaterial surface chemistry influences apoptosis of adherent macrophages both in vitro and in vivo. [12,[53][54][55] Caspase-3, a protein involved in apoptosis signaling, is activated by neutrophils under shear stress and leads to detachment from biomaterials. [56] Caspases are involved in cleaving gelsolin, a protein involved in regulating actin polymerization, and this in turn disrupts adhesion.…”
Section: Apoptosis/anoikis Of Adherent Cells-integrinmentioning
confidence: 99%
“…The surface needs to support fusion. Macrophage fusion on biomaterial surfaces is material dependent [55] indicating that surfaces must have an appropriate array of absorbed proteins in order for adherent cells to undergo the necessary phenotype to fuse into foreign body giant cells. After culturing human monocytes on polystyrene coated with different protein substrates (i.e.…”
Section: Apoptosis/anoikis Of Adherent Cells-integrinmentioning
confidence: 99%
“…biomaterial features, the most important are the material size, surface topology and chemistry, mechanical forces, and the release of degradation products from the implant. 3,[8][9][10]20,21 Hence, the interactions between the implant and bone are mostly determined by the biomaterial surface. Therefore, altering the surface and its features is a way to improve implant -tissue interaction.…”
Section: Discussionmentioning
confidence: 99%